PENGEMBANGAN BUDAYA KUALITAS MELALUI PENERAPAN ISO 9001:2000 DI UNIVERSITAS NEGERI YOGYAKARTA - Dadan Rosana (LPMPP Universitas Negeri Yogyakarta, 2009)
AbstractDeveloping the Quality Culture through the Application of ISO 9001:2000 inYogyakarta State University. One achievement that Yogyakarta State University(YSU) has attained in an attempt to be a world class university is that it hasreceived the ISO 9001:2000 certificate, a standard certification for the quality of auniversitys work units. The meaning of quality management according to ISO9001:2000 is a management system to direct and control an organization in terms ofquality. The certification is carried out to develop an organizations cultureconducive for quality development, called a quality culture. Such a culturecomprises values, beliefs, and expectations owned and developed by members ofthe organizations in terms of quality products and services. A strong qualityculture will support YSUs competitive excellence in the long run.Keywords: quality management, quality culture